2017
DOI: 10.1590/1982-02752017000400011
|View full text |Cite
|
Sign up to set email alerts
|

Validity evidence of the Zulliger-CS in older adults with Parkinson’s disease

Abstract: The ethical principles of psychological assessment include the need to use reliable tests to meet the demands of the emerging population. Therefore, the present study sought to provide evidence of validity of the Zulliger Comprehensive System (Zulliger Test in the Comprehensive System) considering the constructs: self-perception and interpersonal relationships. A total of 61 older adults of both sexes participated in the study; 30 had (p = 0,02, d = 0,50), Conteúdo mórbido (p = 0,025, d = 0,62), Somatório de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…In recent years, advances have been made in the studies with the ZSC at more advanced ages and in the investigation of the cognitive aspects (Aguilar & Graso, 2015;Grazziotin & Scortegagna, 2016a;Gregoletti & Scortegagna, 2017;Miguel et al, 2017;Rien et al, 2017). However, research is insufficient (Cardoso et al,2018;Grazziotin & Scortegagna, 2016b), partly because the legitimacy of the information obtained with psychological tests depends, among other things, on empirical research that certifies the quality of the instruments and their applicability to the intended purposes (Markus & Borboom, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, advances have been made in the studies with the ZSC at more advanced ages and in the investigation of the cognitive aspects (Aguilar & Graso, 2015;Grazziotin & Scortegagna, 2016a;Gregoletti & Scortegagna, 2017;Miguel et al, 2017;Rien et al, 2017). However, research is insufficient (Cardoso et al,2018;Grazziotin & Scortegagna, 2016b), partly because the legitimacy of the information obtained with psychological tests depends, among other things, on empirical research that certifies the quality of the instruments and their applicability to the intended purposes (Markus & Borboom, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the contributions of the ZSC and the limitations of its use in the personality assessment, both at the international level (Aguilar & Graso, 2015;Carpio & Lugón, 2011;Contreras-Milián, González-Pérez, & Herrera-Espinosa, 2016) as well as in the Brazilian context (Cardoso, Gomes, Pacheco, & Viana, 2018;Grazziotin & Scortegagna, 2016a;2016b;Gregoletti & Scortegagna, 2017;Miguel, Zuanazzi, & Villemor-Amaral, 2017;Rien, Scortegagna, Grazziotin, & Bertolin, 2017). However, studies that address cognition in healthy adults (Grazziotin & Scortegagna, 2016a; and those that include older and long-lived adults are rare (Aguilar & Graso, 2015;Grazziotin & Scortegagna, 2018).…”
mentioning
confidence: 99%
“…The authors conclude that the limited number of elderly people who compose the sample reduces the likelihood of detecting potential effects of aging and drives the need for further investigation to examine possible declines in complexity variables related to advancing age. Rien et al (2017), observed a decrease in PER in elderly people with Parkinson's disease, who made up a clinical group, compared to those free of disease that were part of the non-clinical group. The authors understood that due to the need for more care and assistance, as the disease progresses, there are more functional limitations of all kinds, the elderly in the clinical group tend to be less imposing and more passive.…”
Section: Del Prete and A Del Prete 2001)mentioning
confidence: 96%
“…Two recent studies investigated the validity of ZSC in the evaluation of elderly people with chronic diseases. Rien, Scortegagna, Grazziotin and Bertolin (2017) evaluated 61 elderly people, between 60 and 90 years of age, 30 with Parkinson's disease and 31 free of the disease, focusing on self-perception and interpersonal relations. The elderly with Parkinson's disease presented negative self-criticism, feelings of devaluation and dependence, greater reserve and distrust in interpersonal relations, and less use of authoritarian defenses, demonstrated by the significant increase in variables Hd, MOR, Sum V, Fd and lowering in PER.…”
mentioning
confidence: 99%
“…número amostral variou de 1 a 100 participantes, a média de idade variou de 67,5 a 75 anos. Os estudos tiveram como objetivo avaliar o funcionamento psicológico e da personalidade dos idosos(GIL, 2001;OLIVEIRA et al, 2001;COELHO et al, 2010;DALLAGNOL, 2014); a validade e normatização dos instrumentos(BASTOS-FORMIGHIERI;PASIAN, 2012;GREGOLETI;RIEN et al, 2017) e entendimento do psicodiagnóstico (POZZI; BOFF, 2013). Estudos brasileiros com uso de testes projetivos na avaliação de idosos.…”
unclassified